Pengenalan Pendidikan Literasi Keuangan Bagi Anak Usia Dini Pada Kelas Binaan Jurusan Akuntansi Di Buper - Meinarni Asnawi; Cornelia Desiana Matani; Kurniawan Patma (The Community Engagement Journal, 2019)
This community service aims to introduce financial literacy programs for early childhood. Literacy education is important for early childhood so that they are accustomed to financial management well in the future. In Indonesia financial literacy education is still something that is very rarely done, both in the family and school circles, the provision of education about financial literacy has not been done seriously and planned. Service is expected to benefit the knowledge of simple financial management for early childhood through the "saving" pattern. Dedication material is focused on how to introduce the concept of money, utilization and when to do shopping. Financial literacy education will be conducted for pre-school and elementary school children aged 5 - 12 years from study group students and playing in Waena Bupers formed by students majoring in accounting. The teaching method is carried out by the mentoring method by the Teaching Team. The teaching method uses simulation and learning using financial literacy education film media as well as the movements and songs of Ayo Menabung. The simulation of saving is done by practicing saving using piggy banks that are distributed to students. Assistance from the teaching team is carried out continuously with the introduction of financial literacy education that can benefit early childhood and will benefit themselves, their families and society in the future.